Antimicrobial Resistance of Neisseria gonorrhoeae Isolated from Out Patients Presenting with Urethral and Vaginal Discharges at Mbarara Regional Referral Hospital - Owokuhaisa, Judith; Bazira, Joel (Journal of Advances in Medicine and Medical Research, 2019)
Background: Gonococcus is one of the most common sexually transmitted diseases in developing countries and it has become a global health burden, hence a need for effective treatment. However, there is growing trend of antimicrobial resistant strains, in many parts of the world, to the previously effective antimicrobials thus creating serious health concerns. Setting: Mbarara Regional Referral Hospital -South-Western Uganda. Objectives: 1) To determine the prevalence of gonococcus among out patients presenting with urethral and vaginal discharges at MRRH. 2) To determine the level of antimicrobial resistance of gonococcus based on phenotypic methods at MRRH. Design: The study was cross sectional and enrolled 189 participants presenting with urethral and vaginal discharges. The urethral and endo cervical swab samples collected were cultured on Chocolate media supplemented with 5%-10% carbondioxide in candle jar (inoculated plates were placed in a jar and a burning candle placed in the same jar, then closed, by the time the candle went off, that 5%-10% carbondioxide atmosphere would have been created). Isolates obtained were identified according to the laboratory standard operating procedures. Drug Sensitivity Test (DST) on confirmed Neisseria gonorrheae isolates was performed using the Kirby Bauer technique. The colonies of the test organism were emulsified in peptone water and then inoculated on prepared sterile chocolate agar and the following discs were applied to it (Ceftriaxone discs (30μg), Erythromycin (15ug), Ciprofloxacin (10ug) and Penicillin (10IU). The plates were incubated at 37°C for 24- 48 hours under 5% carbon dioxide atmospheres. The Zone of inhibition was seen around an antibiotic disc to which the organism was sensitive. Results: Out of the 189 participants whose urethral swabs and Endo cervical swabs were cultured, 89 were positive cultures (47%), out of which 25 (28%) were found to have gonococcal infection, 64 (72%) patients had other micro-organisms. The prevalence of Neisseria Gonorrhoeae was 13%. In total, 4% of the isolates were resistant to Ceftriaxone, 28% to Ciprofloxacin, 68% to Erythromycin and 80% to Penicillin. A high percentage of resistance was observed against Penicillin (80%) and Erythromycin (68%). Conclusion: Adults aged 18 years and above who present at Mbarara Regional Referral Hospital with urethral or vaginal discharges are more likely to have a Neisseria gonorrhoeae which is resistant to Penicillin and Erythromycin.
Keywords: Neisseria gonorrhoeae; Gonococcus; Antimicrobial; Resistance; Prevalence; Mbarara